The Impact of Teachers’ Attitude and Commitment on Job Performance - Magtoltol, Jenefir; Oropa, Jane (Journal of Interdisciplinary Perspectives, 2025)
This study uses a descriptive correlational research design to investigate the impact of teachers' work attitudes and commitment on job performance. Data were collected through surveys and interviews with 121 teachers from various schools. Results indicate that most participants are female (85%), aged 26-45 (69%), and hold a bachelor’s degree (91%). Findings reveal that highly motivated, enthusiastic, and dedicated teachers demonstrate stronger job performance. Additionally, affective and normative commitment positively correlate with instructional quality and classroom engagement. Institutional support, professional development, and a conducive work environment are key in sustaining motivation and effectiveness. These insights underscore the need for targeted strategies to enhance teacher commitment and work attitudes, ultimately improving educational outcomes.